hOGG1 Ser326Cys and XRCC1 Arg399Gln genetics polymorphism in DNA repair genes by base excision repair pathway (BER) in postmenopausal women with endometrial cancer - Romanowicz-Makowska, Hanna; Smolarz, Beata; Góralczyk, Bożena; Mroziewicz, Kinga; Połać, Ireneusz; Szyłło, Krzysztof; Kulig, Andrzej (Menopause Review/Przegląd Menopauzalny, 2010)
Background : Single nucleotide polymorphisms in DNA base excision repair (BER) system such as: hOGG1 and XRCC1 genes have been extensively studied in the association with various cancers. Material and methods : In the present study hOGG1 Ser326Cys and XRCC1 Arg399Gln gene polymorphisms in endometrial cancer patients and controls were investigated. Results : There were no significant (p > 0.05) differences in the frequencies of genotypes or alleles of hOGG1 genes between endometrial cancer women and controls. However, the frequency of the XRCC1 399Gln allele was significantly greater in endometrial cancer subjects as compared with controls (p = 0.035) [OR 1.25 (95% CI 1.02 to 1.55). The distributions of genotypes and alleles of the hOGG1 and XRCC1 genes were not significantly associated with the different grades of endometrial cancer (p > 0.05). Conclusion : This study suggested that XRCC1 Arg399Gln polymorphism may play an important role in endometrial cancer development in the Polish population.